2008
DOI: 10.1086/587487
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activities of Cardiac Matrix Metalloproteinases Matrix Metalloproteinase (MMP)–2 and MMP‐9 Are Associated with Mortality during the Acute Phase of ExperimentalTrypanosoma cruziInfection

Abstract: The strong inflammatory reaction that occurs in the heart during the acute phase of Trypanosoma cruzi infection is modulated by cytokines and chemokines produced by leukocytes and cardiomyocytes. Matrix metalloproteinases (MMPs) have recently emerged as modulators of cardiovascular inflammation. In the present study we investigated the role of MMP-2 and MMP-9 in T. cruzi-induced myocarditis, by use of immunohistochemical analysis, gelatin zymography, enzyme-linked immunosorbent assay, and real-time polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 45 publications
9
73
0
4
Order By: Relevance
“…Polyakova et al (14) showed that elevated expression of MMP-2 and MMP-9 is associated with collagen maturation in heart failure, demonstrating an important role of these enzymes in fibrosis through collagen configuration, activation, and deposition. In experimental models of Chagas disease, high MMP-2 and -9 proteolytic activity had already been described, which suggested an important role for MMPs in T. cruzi-induced acute myocarditis (17). Here, we showed elevated levels of these enzymes in chronic Chagas disease.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Polyakova et al (14) showed that elevated expression of MMP-2 and MMP-9 is associated with collagen maturation in heart failure, demonstrating an important role of these enzymes in fibrosis through collagen configuration, activation, and deposition. In experimental models of Chagas disease, high MMP-2 and -9 proteolytic activity had already been described, which suggested an important role for MMPs in T. cruzi-induced acute myocarditis (17). Here, we showed elevated levels of these enzymes in chronic Chagas disease.…”
Section: Discussionsupporting
confidence: 68%
“…3B). The participation of MMPs in immune cell migration has been demonstrated (17), and their production by lymphocytes could be justified, especially because CD8 ϩ T lymphocytes are the main inflammatory-cell source in the heart during Chagas disease (42). Other immune cells, such as neutrophils (16), and many different cell types, including cardiomyocytes, fibroblasts, and endothelial cells (16,27), are able to produce and secrete MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression of MMP2/MMP9 and cathepsin B in chagasic hearts had been noted (26) and implicated in ECM degradation, gradual slippage of ventricular layers, and formation of an apical aneurysm in the heart, a hallmark of disease (27,28). Macrophages incubated with sera from chronically infected mice exhibited a 3-fold increase in MMP2/MMP9 activity compared to that in normal controls (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Metallopeptidases homologous to the gp63 of Leishmania spp. are present in T. cruzi, as well as two metallocarboxypeptidases belonging to the M32 family, before found only in prokaryotes (Bonaldo, 1991;Lowndes, 1996;Burleigh, 2002;Cuevas, 2003;Nogueira de Melo, 2004;Gutierrez, 2008;Niemirowicz, 2007;Niemirowicz, 2008;Kulkarni, 2009). The most abundant among these enzymes is cruzipain (Cz), also known as GP57/51 or cruzain (the recombinant catalytic domain of cruzipain) a cysteine peptidase (CP) expressed as a mixture of isoforms.…”
Section: Peptidasesmentioning
confidence: 99%